Fuelwood Characteristics of Five Species Grown in Merauke Forest - Nunik Sri Wahyuni; Joko Sulistyo (Masyarakat Peneliti Kayu Indonesia, 2016)
Papua has a large area of production forests, such as in Merauke. These forests provide great benefits for the pulp and wooden industries, which generate a large amount of biomass waste. Therefore, this study aimed to investigate the proximate analysis, specific gravity, calorific value, and Fuelwood Value Index (FVI) of wood and bark of five species, namely Acacia mangium Willd, Acacia crassicarpa A. Cunn, Eucalyptus pellita F. Muell, Melaleuca viridiflora Sol. Ex Gaertn, and Lophostemon suaveolens Sol. Ex Gaertn. The calorific value ranged from 4,066 to 5,435 cal/g, while the FVI values ranged from 4.04 to 76.41. The highest calorific value was observed in the bark of Melaleuca viridiflora, while the highest fuelwood value index was observed in Eucalyptus pellita wood. Furthermore, the calorific value of wood was higher compared to the bark in all species. There was no significant correlation between specific gravity, calorific or FVI value. It is noticed that a strong correlation (r = -0.92*) was observed between the calorific value and volatile matter in the bark. Based on the proximate analysis results, only the moisture content level was significantly correlated with the calorific value of wood or bark.